Approaches to participation and the research on the youth in Croatia - Čaldarović, Ognjen (Array, 2004)
Interpretation of the results of a focus group analysis technique with a group of Jewish youth held in Jewish community Zagreb (December, 2003). Results shows what are the major orientation of Jewish youth in Croatia concerning the issues on social integration, orientations towards Europe and some other issues.